Analysis of ischemic stroke burden in Asia from 1990 to 2019: based on the global burden of disease 2019 data - Zhang, Xueli; Lv, Hengliang; Chen, Xin; Li, Maoxuan; Zhou, Xiaojing; Jia, Xiaoying (Frontiers in Neurology, 2023)
Background: Ischemic stroke has the characteristics of high morbidity, mortality, and recurrence rate. The aim was to describe and assess the burden of ischemic stroke in Asia based on the Global Burden of Disease (GBD) 2019 data, and provide crucial scientific foundation for the prevention and control of ischemic stroke.The data we used was based on the GBD 2019 in this study. The indicators we used were derived from the following methods: the incidence of ischemic stroke was estimated using Disability Model for the Global Burden of Disease Study-Mixed Effects Regression (DisMod-MR), a Bayesian metaregression disease modeling tool; the non-specific codes of all available data on mortality were corrected and used to estimate mortality rates for ischemic stroke, and the Cause of Death Ensemble model was used to estimate mortality rates; the Disability Adjusted of Life Years (DALYs) was the sum of years lived with disability(YLD) and the years of life lost(YLL), which quantified the health loss due to specific diseases and injuries. In addition, joinpoint regression was adopted to analyze the temporal trend of ischemic stroke from 1990 to 2019 in Asia. India, Indonesia, and Japan ranked with the highest burden among the countries, with a concentration of the high burden population were still in the elderly groups.Based on our study, it is evident that the burden of ischemic stroke exists substantially and exhibits variations in the aspect of age, gender, and geographical region in Asia. Without targeted implementation of population-wide's primary strategies of prevention and control , the burden of ischemic stroke is likely to worsen significantly in the future.